1997
DOI: 10.1016/s0014-5793(97)01311-2
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of the plant mitochondrial matrix located HSP70 chaperone and its role in protein import

Abstract: Changes in the level of the mitochondrial chaperone mtHSP70 have been investigated in pea (Pisum sativum) leaf mitochondria by Western blot analysis and quantified by scanning densitometry. As pea leaves develop (from 6 days to 30 days of age) the levels of mtHSP70 decrease. Analysis of the levels of the a subunit of the FxATPase show that the levels of this protein remain constant throughout the same developmental period, whereas the levels of the alternative oxidase increase. In vitro import of the alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…It has long believed that MPI is an unregulated event, until recent evidence from plant studies showed that mitochondrial internalization of proteins is influenced by light-dark cycle and developmental cues (39). The next section will address the regulation of MPI in oxidative stress conditions.…”
Section: Candas and LImentioning
confidence: 99%
“…It has long believed that MPI is an unregulated event, until recent evidence from plant studies showed that mitochondrial internalization of proteins is influenced by light-dark cycle and developmental cues (39). The next section will address the regulation of MPI in oxidative stress conditions.…”
Section: Candas and LImentioning
confidence: 99%
“…, 2008). Plant mitochondrial import has been shown to be susceptible to rhythmic and developmental control, but the basis for this regulation is not known (Dudley et al. , 1997; Glaser et al.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the import machinery itself, very little is known about the regulation of mitochondrial import (Glaser et al, 1998;Bolender et al, 2008). Plant mitochondrial import has been shown to be susceptible to rhythmic and developmental control, but the basis for this regulation is not known (Dudley et al, 1997;Glaser et al, 1998). Import of proteins into mitochondria needs to be regulated in close correlation with the developmental stage and physiological requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies reported that purified tobacco mitochondria did not import proteins [12–14], it was subsequently shown that this was due to the fact that import into isolated tobacco mitochondria occurs in a rhythmic manner [15]. Developmental regulation of protein import has been reported in pea leaf, which was proposed to be due to a reduction in the mtHSP 70 [16]. In animals, regulation of protein import has also been reported.…”
Section: Introductionmentioning
confidence: 99%